Typical Suburban Scene, Trinidad, W.I. - (:unkn) unknown (Picture-Point Publications, New York, N.Y., 2009)
A street passing through a village with houses and coconut trees on either sides and tall mountains in the background. The postcard is addressed to Mr. Elmer Coles, Pitman, N.Y. Affixed to the postcard is a Trinidad and Tobago 12 cents stamp, postmarked January 12th, 1967.
Colour; Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Streets; Villages; 1967